THE INNOVATION ENGINE: HOW AI IS RESHAPING BUSINESS MODELS AND ORGANIZATIONAL EFFICIENCY - Nofiyanti, Nofiyanti; Winanti, Winanti; Fajrin, Andira; Aks, Safriadi M. Yunus; Farhan, Akhmad; Kamar, Karnawi; Himmy Azz, Istajib Kulla; Asbari, Masduki (Jurnal Bisnis Manajemen dan Akuntansi, 2025)
Today's digital transformation is heavily influenced by the presence of artificial intelligence (AI), which significantly changes the way businesses run while improving organizational efficiency. This research explores the utilization of AI in various industries, as well as the extent to which AI plays a role in driving business model innovation and improving company operational performance. By combining several approaches, this research systematically reviews scholarly articles from 2019 to 2024 as well as related digital book literature. The results show that AI has three main roles. First, it improves organizational efficiency through automation, smarter data processing, and cost savings. Second, driving business model change through service personalization, demand prediction, and integration with digital platforms. Third, it accelerates organizational learning in the process of business innovation. In addition to the technological and economic benefits, the study also highlights the importance of ethical aspects and participation in the application of AI, in order to minimize risks such as algorithm bias and potential decline in public trust. In conclusion, AI is not just a technological tool, but a strategic piece that can reshape organizational structures and business patterns. To effectively implement AI, organizations need to build digital capabilities, cultivate learning, and implement responsible governance.